Fatigue Fracture Properties and Morphology of Polyoxymethylene (POM) Plates Produced under Moderate Processing Conditions. (4th November 2018) - Berer, M.; Halb, M.; Feuchter, M.; Pacher, G.; Pinter, G.
Abstract : The present study was inspired by different industry projects in which a strong dependence of the fatigue fracture performance of POM on the processing conditions was observed. To examine the relationships under more reproducible conditions, plates of two different POM homopolymer resins (one significantly nucleated) were produced by compression molding and by injection molding under moderate conditions. For the injection molding, three different mold temperatures were used. At specific locations, the plates were analyzed concerning their hierarchical structure on the micro- and nanolevel and concerning their fatigue fracture performance. For the fatigue fracture performance, the dependence on the processing conditions was rather small for the nucleated resin but much more significant for the other resins. This dependence could not be related to morphological effects only, and thus, a combined effect of morphology and residual stresses was assumed.